SKRINING FITOKIMIA DAN UJI TOKSISITAS EKSTRAK DAUN KATUK (Saoropus androgenus (L.) Merr.) TERHADAP LARVA UDANG ARTEMIA SALINA: POTENSI FITOFARMAKA PADA IKAN - Dyahruri Sanjayasari; Wiranda G Pliliang (Berkala Perikanan Terubuk, 2011)
Phytochemical screening and Brine Shrimp lethality test of katuk leavesextract had been done against Artemia salina Leach. The aims of this study is toscreen potentially bioactive extract of katuk leaves as an effort to find out thechemical substances responsible for the toxic effect. Katuk leaves (Saoropusandrogenus (L.) Merr.) was extracted by ethanol 96%, to find the rendemen ofkatuk leaf extract. Phytochemical screening was done qualitatively. The toxicitytest was used experimental design with 4x3 treatments. The concentration extract50 ppm, 100 ppm, 500 ppm and 1000 ppm, with 3 repetitions. Its effect was testedagainst A. salina, L (Brine Shrimp Test). The result of phytochemical screeningshowed that compounds in the extract of katuk leaves (Saoropus androgenus (L.)Merr.) contained of sterol after the addition of diethyl ether. Katuk leaf extractalso contained phenol substance such as tannin, saponin and flavonoid. The resultof the study shows that extract of katuk leaves (Saoropus androgenus) was toxicbecause it was able to kill more than 50% larva of A. salina, L at the concentrationless than 1000 ppm. The LC50 of katuk leaves extract (Saoropus androgenus (L.)Merr.) was shown at 954.01 ppm.